Super graphic a visual guide to the comic book universe - Leong, Tim (Chronicle Books LLC, 2013)
The comic book universe is adventurous, mystifying, and filled with heroes, villains, and cosplaying Comic-Con attendees. This book by one of Wired magazine's art directors traverses the graphic world through a collection of pie charts, bar graphs, timelines, scatter plots, and more. Super Graphic offers readers a unique look at the intricate and sometimes contradictory storylines that weave their way through comic books, and shares advice for navigating the pages of some of the most popular, longest-running, and best-loved comics and graphic novels out there. From a colorful breakdown of the DC Comics reader demographic to a witty Venn diagram of superhero comic tropes and a Chris Ware sadness scale, this book charts the most arbitrary and monumental characters, moments, and equipment of the wide world of comics.